Teaching Algorithms for Visually Impaired and Blind Students using Physical Flowcharts and Screen Readers - Pereira, Rodolfo M.; da Silva, Felippe Fernandes; Silla, Carlos N. (Proceedings - Frontiers in Education Conference, 2018)
This Innovative Practice Full Paper is grounded in the theme of teaching algorithms and programming to students with Special Educational Needs and Disabilities (SENDs) which is an increasingly difficult task for educators. The inclusion of SENDs in this context, makes the teaching task even more challenging, since in addition to the students' physical limitations, there is also the non-preparation of the teachers for specialized education. Among the SENDs, the students with visual impairment present one of the biggest obstacles in teaching algorithms. Considering the previously described context, this work proposes a method that uses Physical Flowcharts and Screen Readers in order to assist teaching algorithms to Visually Impaired students. To investigate the effectiveness of our method, a study was carried out in a Visually Impaired group of five students using the proposed method. The results of this study indicate that our method is promising and may be used in the future to help students with this kind of special needs.